A Quasi 2D Model of a High Temperature Polymer Fuel Cell for the Interpretation of Impedance Spectra. Issue 6 (15th September 2014) - Baricci, A.; Zago, M.; Casalegno, A.
Abstract Electrochemical impedance spectroscopy is a widely recognized tool for in situ diagnostics of polymer fuel cells. The main drawback of this measurement is that it includes several features, which are not directly related to physical phenomena and the interpretation is often difficult. In this work, a physical quasi 2D model is applied to experimental data of a high temperature proton exchange fuel cell based on polybenzimidazole doped with phosphoric acid. The quasi 2D approach is applied in order to decrease the computational cost of the model, without decreasing the prediction capability. The model is able to simulate polarization curves and impedance spectra and it is fitted on six polarization data and impedance spectra recorded in different conditions. The model is able to capture the main features of a typical spectrum of a polybenzimidazole based high temperature polymer fuel cell. A sensitivity analysis is also performed on the model parameters to show the effect of each physical parameter.